Multiplicity of constant kappa light chain genes in the rabbit genome: a b4b4 homozygous rabbit contains a kappa-bas gene. - Heidmann, O (1983)
We have constructed a genomic library of homozygous b4b4 rabbit DNA in the pJB8 cosmid vector. Clones containing Ckappa-like sequences were screened with a b4 cDNA probe and were characterized by restriction mapping. One of the clones contained a Ckappa sequence different from the b4 allotype normally expressed by the animal. We report here the nucleotide sequence of this gene and show that it probably corresponds to a kappa-bas form of the Basilea allotype. It appears to be a structurally complete gene without any stop codons within the coding region and containing the dinucleotide AG as a splice site acceptor for the J-C junction, just 5' of the coding block. Comparison with the b4 cDNA nucleotide sequence shows a separate evolution of the Ckappa-coding and 3'-untranslated sequences, since the 3'-untranslated regions are more conserved than the coding regions. Genomic blot analysis would suggest that the kappa-bas gene is isotypic in the domestic rabbit population, since it lies within a genomic EcoRI or PstI restriction fragment, which was shown to be common to all homozygous b4, b5, b6 and b9 rabbit DNAs.